Hubungan Durasi Bekerja Dengan Kualitas Tidur Pada Ojek Online - Kuntoro, Widhi; Dini, Kris Linggar (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
RELATIONSHIP DURATION WORKING WITH SLEEP QUALITY ON OJEK ONLINEWidhi Kuntoro 1, Kris Linggardini 21.2 Faculty of Health Sciences, Muhammadiyah University PurwokertoEmail: Widhikun29@gmail.comAbstractIntroduction: The prevalence of quality improvement for each improvement is also related to various causes. One cause of improvement is poor sleep quality. If adequate sleep is obstructed, it can cause accidents. The phenomenon of online motorcycle taxi in the era of application-based globalization meets the most in every place. The collection of motorcycle taxi drivers where they are 24 hours on the road is what causes the online motorcycle taxi drivers to sleep less.Objective: The general objective in this research is to study the relationship of work duration with sleep quality on online motorcycle taxi.Method: This research is a quantitative descriptive study using cross sectional method. The sample of this study was an online motorbike rider which was put forward by researchers as many as 50 riders with sequential sampling techniques. The measuring instrument used was a questionnaire sheet.Results: The sex characteristics of the respondents were mostly 47 male respondents (86.0%). The age characteristics of most of the early adults were 36 respondents (72.0%). Most of the high school education is 29 respondents (48.0%). 74.0% online motorcycle taxi drivers have poor sleep quality. Meanwhile, on the characteristics of the duration of work, it shows that the majority of online motorcycle taxi drivers work> 15 hours / 3 days (74.0%) of respondents. The results of the analysis of work duration variables with sleep quality indicate a significant relationship, with a p value = 0,000.Conclusion: There is a relationship between the duration of work and the quality of sleep at an online motorcycle taxi.Keywords: Duration of work, quality of sleep